Maritime studies higher education quality (MSHEQual) : the design of maritime studies higher education quality dimensions - Chia, Ying Ying (Nanyang Technological University, 2021)
This paper aims to identify the quality dimensions of maritime studies higher education programmes to form the MSHEQual model. The quality dimensions were identified from reviewing the literature. Subsequently, the administration of an online survey was done on 103 Maritime students at Nanyang Technological University, Singapore. Thereafter, exploratory factor analysis was used. A Six-Factor solution was generated containing 29 measurement items for the MSHEQual model. Overall, students’ quality perception in competencies of faculty members has the highest factor mean value followed by learning & teaching environment, supporting activities, student industrial exposure, technology integration and industry-aligned & innovative curriculum, respectively. Overall, maritime students’ quality perception of the quality dimensions were relatively good (factor mean value > 4). Additionally, maritime students’ quality perception for the six factors differs. Hence, there is a need for maritime higher education programmes to prioritise which factors to allocate their limited resources. Hence, to decide which factors to prioritise, a further examination on the effects of the quality dimensions on student satisfaction is recommended for further studies. Additionally, the MSHEQual model can be a measurement tool for maritime studies higher education programmes to assess the quality of their programme.